Comparative Study Of Solar Drying And Freeze Drying Methods In Amino Acid Content Of Crude Ficin Enzyme From Ficus Aurata (Miq.) - Ismed Ismed; Rina Yenrina; Hasbullah Hasbullah; Daimon Syukri; Yusniwati Yusniwati (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This work aimed to analyze the profiles of amino acids in the ficin enzyme isolated from Ficus aurata (Miq.), and to determine the efficiency of these amino acid concentrations under two types of drying – solar drying and freeze drying. Methodology: The enzyme ficin was obtained from fig tree, and the presence of amino acids was determined by UPL chromatography. The applied methods of drying were solar and freeze. However, the primary objectives were aimed at investigating the influence of these treatments on the level of amino acids present in all the samples. Results: The findings indicated that freeze drying techniques retained more amino acids in figs than was observed in the case of solar drying. In particular, the amount of L-glutamic acid in freeze drying was 2.39 mg/g, while that of solar drying was 1.43 mg/g. Similar results were observed in L-lysine and L-aspartic acid, which were relatively higher in freeze drying than solar drying, with concentrations of 2.43 mg/g and 2.55 mg/g, respectively, as opposed to 0.99 mg/g and 1.76 mg/g in solar drying. Besides, freeze drying showed better L-serine, L-phenylalanine, and L-histidine preservation. Findings: It was observed that freeze drying gave the best opportunity to reduce the loss of amino acid of the ficin enzyme. The drying method, in particular, resulted in a concentration of some important amino acids like L-glutamic acid, L-lysine, L-aspartic acid, L-serine and L-phenylalanine, and L-histidine as compared to solar drying. Novelty: This study focused on different types of solar energy and freeze energy economic systems in enzymatic activities in the ficin enzyme extracted from Ficus aurata (Miq.). The novel contribution of this research lies in its objective, which is to show how the drying methods used affected the retention of the most influential and critical amino acids in the enzymatic processes. Originality: The novel aspect of the study was the attachment of ultra vortices to different drying techniques, such as solar drying and freeze drying in select ficin enzymes from Ficus aurata. It opens up a new perspective toward the development of drying parameters for the enhancement of important enzymatic characters from this particular variety. Conclusion: This research considers the changes in amino acid content during the drying of ficin enzyme from Ficus aurata through different drying methods. It is shown that freeze drying enhances the retention of critical amino acids and is thus one of the most efficient methods for the enzymatic processing of this plant species. Type of Paper: Empirical research paper.